2003
DOI: 10.2298/aci0303154i
|View full text |Cite
|
Sign up to set email alerts
|

Early complications of thyroid surgery: Analysis of 2100 patients

Abstract: Background/Aims. Thyroid gland surgery today is not saddled with high incidence of main complications. Miscellaneous surgical institutions with different surgical approach, operative technique and radicality have published reports with great discrepancy in incidence of complications, analyzing them with different methods of diagnosis and result evaluation. In the same way it is well known that higher latitude of operative procedure gave better control of thyroid diseases, but it can be accompanied with more co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 127 publications
3
19
0
Order By: Relevance
“…It is therefore not surprising that postoperative bleeding is a complication of thyroid surgery. The findings of the present investigation are consistent with published results from other large studies1, 14–18. The present analysis showed variability in individual surgeon performance, although they all had experience of at least 300 thyroid operations.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It is therefore not surprising that postoperative bleeding is a complication of thyroid surgery. The findings of the present investigation are consistent with published results from other large studies1, 14–18. The present analysis showed variability in individual surgeon performance, although they all had experience of at least 300 thyroid operations.…”
Section: Discussionsupporting
confidence: 91%
“…Postoperative bleeding is an important complication after thyroidectomy and may be the limiting factor for outpatient thyroid surgery or early discharge from hospital1–4. Numerous articles have reported on postoperative bleeding after thyroid operations, with an incidence ranging from 0 to 6·5 per cent1, 3, 5–21. A review of publications containing large cohorts of more than 1000 patients from single centres found rates of 0·3–1·2 per cent.…”
Section: Introductionmentioning
confidence: 99%
“…Thyroid surgery is relatively safest surgery and the mortality rates has been fallen in recent years from 40% in 1800s to 0-0.05% in recent years, owing to better preoperative preparations and improved surgical techniques resulting in minimum complications [18][19][20]. Our data shows differs in these fi gures as we found 3 deaths and mortality rate of 0.14% in 2094 patients due to our large sample size.…”
Section: Discussionmentioning
confidence: 58%
“…Mortality rate from thyroid surgery during the 1800s was approximately 40%. Most deaths were caused by infection and hemorrhage but nowadays the incidence of death ranges from zero to 0.5% [8,14,15]. Thyroid surgery in recent years is generally considered quite safe owing to better preoperative preparation and proper surgical techniques that kept complications at a minimum to less than 2-3% [16].…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that postoperative hemorrhage and hematoma formation were seen in three patients (2.5%) in ST group while four patients (3.3%) in T group with insignificance statistical difference that came in concordance with many reports. The rate of postoperative hemorrhage varied from 0.56% to 1.1% in many series [9,14,16,[24][25][26] while others described their experiences of thyroidectomies with hemorrhage up to 2.5% [27].…”
Section: Groupmentioning
confidence: 99%